Water managed properties of apple and pear trees based on lysimeters - Riczu, Péter; Szőllősi, Nikolett; Tamás, János; Zsembeli, József (Acta Agraria Debreceniensis, 2011)
A significant proportion of the aboveground green and dry weight of the plant is constituted by foliage. The canopy is an important factor of plant growth. On the one hand, the canopy absorbs solar energy, which is necessary for photosynthesis; on the other hand, it accumulates the nutrients absorbed by the roots, and most of the water-loss occurs through the foliage. The determination of the full canopy is not an easy target. In our research, we developed a measurement method to determine the leaf area. With the parameters of the examined tree (leaf length and maximum width) and the data of the ADC AM 100 leaf area scanner, we determined the k-value, with which we can easily and fast evaluate the leaf surface. Furthermore, we defined from the water balance of compensation lysimeters the cumulative transpiration of fruit trees and the efficiency of water use of trees. From the examined trees were made a 3D depiction, which show the shape, branching and the location of trees.